2016
DOI: 10.17533/udea.rccp.v29n1a01
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic factors affecting sheep meat quality: a review

Abstract: SummaryThe quality of meat is a multifactorial parameter dependent on the perspective and goals of the link in the production chain. Generally, a variety of factors directly or indirectly affect the quality characteristics of meat and, therefore, the value of meat products. Often, the literature divides the interfering factors into intrinsic and extrinsic. Intrinsic factors are related to animals; therefore, intrinsic factors are less variable. These factors include breed, sex, age, weight, genes, and type of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 72 publications
1
22
1
1
Order By: Relevance
“…Color is the main attribute used to appreciate meat freshness, and consumers tend to prefer a pale or pink color for light lamb meat [5], and accept darker meat from older lambs [3]. In line with this study, other authors [3,7,9] found an increased redness, related to the higher content of myoglobin [1], in meat from older and heavier lambs. The levels of red color of meat from Valle del Belice lambs were within the commonly detected ranges; in this regard, the redness of the 90L meat was slightly higher than that observed in 100-day-old Comisana lambs [43], and comparable to that found in Barbaresca lambs of both 100 [41] and 130 days of age [42], and in 5-month-old Fabrianese lambs [3], whereas the darker meat from 120-day-old Valle del Belice lambs approached the redness values observed in 130-day-old Comisana lambs [40] and also in 60-day-old Bergamasca light lambs [9].…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…Color is the main attribute used to appreciate meat freshness, and consumers tend to prefer a pale or pink color for light lamb meat [5], and accept darker meat from older lambs [3]. In line with this study, other authors [3,7,9] found an increased redness, related to the higher content of myoglobin [1], in meat from older and heavier lambs. The levels of red color of meat from Valle del Belice lambs were within the commonly detected ranges; in this regard, the redness of the 90L meat was slightly higher than that observed in 100-day-old Comisana lambs [43], and comparable to that found in Barbaresca lambs of both 100 [41] and 130 days of age [42], and in 5-month-old Fabrianese lambs [3], whereas the darker meat from 120-day-old Valle del Belice lambs approached the redness values observed in 130-day-old Comisana lambs [40] and also in 60-day-old Bergamasca light lambs [9].…”
Section: Resultssupporting
confidence: 74%
“…Several studies have indicated that heavier lamb carcasses show a better conformation [5], and higher dressing percentage [3] and meat: bone ratio [6], thus giving a superior meat yield. However, lamb meat from heavier carcasses is characterized by a higher lipid content [7] due to the increased intramuscular fat deposition, which can have negative effects on meat quality with regard to sensory attributes [8] and health properties related to fatty acid profile [9].…”
Section: Introductionmentioning
confidence: 99%
“…Meat juiciness is dependent on water and fat contents [236]. de Lima et al [237] reviewed the intrinsic factors affecting sheep meat quality and reported that the level of marbling affects different sensory attributes, especially juiciness. Cloete et al [238] evaluated sheep breeds and reported that the lower proportion of IMF in meat from Merino breed was responsible for lower sensory score for initial juiciness and lasting succulence compared to other sheep breeds.…”
Section: Juicinessmentioning
confidence: 99%
“…LISTRAT et al (2016) also reviewed the biochemical and structural characteristics of muscle fibers, intramuscular connective tissue, and the intramuscular fat appear to play independent role, suggested that properties of those various muscle components could independently modulate by the genetics and or environmental factors to achieve production efficiency and improve quality of meat. Other authors reported that typically, the selected breeds for meat production have a greater number of muscle fibers and a smaller amount of intramuscular fat per unit area of muscle (BUNGER et al, 2009;HOPKINS et al, 2011;DE LIMA et al, 2016). MCPHEE et al (2008) found that the amount of intramuscular fat significantly increased as the sheep became older and fatter; however, these differences were quantitatively small.…”
Section: Discussionmentioning
confidence: 99%